A Framework for Improving Web 2.0 Interaction Design - Hajarian, Mohammad (Ciência e Natura, 2015)
Interaction design of websites has been changed during last decade, yet principles of interaction design and frameworks seem not to be updated based on the new technology and findings. Moreover most of the web developers are just trying to copy other famous companies’ works, because they do not have any idea what standards they have to follow, and this is not because there is not any frameworks and standards but it is because these frameworks do not meet new technology requirements. Although most of the research on interaction design did not consider elements such as Ajax pages and different type of device’s screen size such as tablets and phones (and they influence on web page design), in this research author has reviewed different principles of interaction design in different studies and based on these studies and recent changes in technology, suggested a new framework. Furthermore two round study was performed on a social network website, one before implementing this framework and the other one after implementing it. Additionally findings were evaluated to show that by implementing this framework in web design not only developers, but users will benefit from it.